QUALITY CONTROL ANALYSIS OF BOTTLED DRINKING WATER PRODUCT IN PT.XYZ MINAHASA UTARA - Endey, Mabella C. Z.; Lapian, S.L.H.V. Joyce; Tumewu, Ferdinand . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Companies in this era of globalization are required to compete with each other. Consumers now prefer the products with good quality. In order to produce better products and mitigate defect in products, every company must implement a quality control system. Company will find means to implement a quality control system that is capable and reliable. One of the methods is using Statistical Process Control (SPC). The case studied in this research was the bottled drinking water product in PT.XYZ in Minahasa Utara. The SPC is including Control Charts, Pareto Diagrams and Fishbone Diagrams (Cause and Effect Diagram). Based on the analysis of control chart indicates that the process is out of control. This can be seen in the graph control where there is still a lot of outlier data. Based on Pareto diagram, repair needs priority is for the dominant type of defect is lid (75%). Based on the analysis of the factors causing defect by fishbone diagram, the types of defects originating from the methods, machines, and labor. Thus the company can take to minimize the prevention and repair of defects and improve product qualityKeywords: quality control, damaged product, bottled drinking water, contol chart, pareto diagram, cause and effect diagram